2012
DOI: 10.3171/2012.1.focus11352
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hemorrhage secondary to intravenous and endovascular intraarterial revascularization therapies in acute ischemic stroke: an update on risk factors, predictors, and management

Abstract: Intracerebral hemorrhage (ICH) secondary to intravenous and intraarterial revascularization strategies for emergent treatment of acute ischemic stroke is associated with high mortality. ICH from systemic thrombolysis typically occurs within the first 24–36 hours of treatment initiation and is characterized by rapid hematoma development and growth. Pathophysiological mechanisms of revascularization therapy-induced ICH are complex and involve a combination of several distinct processes, including the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 55 publications
0
37
0
1
Order By: Relevance
“…1 The pathophysiology of cerebral hemorrhage associated with reperfusion therapies involves the disruption of the BBB, procedure-related direct vessel damage, and the toxicity secondary to thrombolytic drugs. 22 In our series, the presence of signs of BBB disruption in DE-CT was associated with longer duration of the procedures and higher number of thrombectomy device passes, as well as with preintervention stroke severity and longer duration of ischemia. Longer procedure times were highly correlated with the number of passes of thrombectomy devices, as a marker of direct procedure-related vessel damage, and probably with enhanced exposure to intra-arterial contrast.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…1 The pathophysiology of cerebral hemorrhage associated with reperfusion therapies involves the disruption of the BBB, procedure-related direct vessel damage, and the toxicity secondary to thrombolytic drugs. 22 In our series, the presence of signs of BBB disruption in DE-CT was associated with longer duration of the procedures and higher number of thrombectomy device passes, as well as with preintervention stroke severity and longer duration of ischemia. Longer procedure times were highly correlated with the number of passes of thrombectomy devices, as a marker of direct procedure-related vessel damage, and probably with enhanced exposure to intra-arterial contrast.…”
Section: Discussionmentioning
confidence: 78%
“…68 (13) 29 (43) 18 (27) 45 (67) 20 (30) 31 (46) 23 (34) 36 (54) 153 (23) 127 (113-155) 16 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) 8 (7)(8)(9) 31 (46) 36 (54) 277 47 50 ( (22) 27 (46) 9 (15) 25 (42) 15 (25) 22 (37) 141 (24) 119 (101-135) 13 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) 44 (75) 41 (70) 18 (31) 263 300 30 Poor outcome p N=50 69 (12.3) 20 (40) 12 (24) 34 (68) 17 (34) 24 (48) 17 (34) 26 …”
Section: Poor Outcome P N=67unclassified
“…5,6 Of those mechanisms, the severity of brain ischemia can be reliably quantified using dynamic contrast-enhanced magnetic resonance imaging (MRI) or computerized tomography (CT) by measuring cerebral blood flow (CBF), cerebral blood volume (CBV) or time-based variables such as Tmax, mean transit time (MTT), time to peak (TTP) or delay time (DT). MRI-based clinical studies of patients with acute stroke treated or not with thrombolysis have shown that very severe reductions of CBV (termed as Very Low CBV) are strongly associated with the risk of PH, [7][8][9] particularly when delayed reperfusion occurs after thrombolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Since we evaluated the effectiveness of endovascular treatment on the top of standard therapy, this finding is not surprising and may be linked to the reperfusion of the ischemic area, in which there is a blood-brain-barrier alteration triggered by ischemia [29]. On the other hand, like in most reperfusion studies in stroke patients, this increased risk did not offset the positive effect of the treatment.…”
Section: Discussionmentioning
confidence: 85%